2016
DOI: 10.1682/jrrd.2015.04.0065
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the inertial sensor-based Timed “Up and Go” test in individuals affected by stroke

Abstract: Abstract-The instrumented Timed " Up and Go" test (iTUG) has the potential for playing an important role in providing clinically useful information regarding an individual's balance and mobility that cannot be derived from the original singleoutcome Timed "Up and Go" test protocol. The purpose of this study was to determine the reliability and validity of the iTUG using body-fixed inertial sensors in people affected by stroke. For test-retest reliability analysis, 14 individuals with stroke and 25 nondisable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 44 publications
1
70
0
Order By: Relevance
“…Wuest et al [15] found good test-retest reliability of IMU-based TUG metrics in patients with stroke, with ICC values generally above 0.9 for TUG sub-tasks with the exception of sit-to-walk (equivalent to our sit-to-stand sub-task) which had a poor reliability (0.4). This finding agreed with our data to some extent, as it was the longer 5 m test that experienced the lower sit-to-stand reliability in our study, and Wuest’s study used a 7 m TUG test.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Wuest et al [15] found good test-retest reliability of IMU-based TUG metrics in patients with stroke, with ICC values generally above 0.9 for TUG sub-tasks with the exception of sit-to-walk (equivalent to our sit-to-stand sub-task) which had a poor reliability (0.4). This finding agreed with our data to some extent, as it was the longer 5 m test that experienced the lower sit-to-stand reliability in our study, and Wuest’s study used a 7 m TUG test.…”
Section: Discussionmentioning
confidence: 90%
“…Several groups have explored wearable sensors—IMUs specifically—as a potential approach for enabling the quantification of sub-task performance measures of the TUG and have demonstrated that these sensor-based metrics can discriminate between healthy controls and patient populations [10,11,12,13,14,15,20]. These devices have been shown to be useful for assessments in community dwelling seniors with dementia and/or history of falling when incorporated within a clinical protocol, such as a single- and dual-task paradigm [16,17,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrumented timed-up and go (iTUG), APDM Mobility Lab system (APDM, Inc., Portland, USA), a set of portable inertial sensors and software were used to classify the components of 7 m TUG. The iTUG is reliable and valid to measure TUG performance in several group of patients with neurological diseases 16,20 . The iTUG has excellent testretest reliability (intraclass correlation coefficients range 0.43-0.99) and duration components of the TUG were valid to differentiate performance between patients with stroke and healthy persons 20 .…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The iTUG is reliable and valid to measure TUG performance in several group of patients with neurological diseases 16,20 . The iTUG has excellent testretest reliability (intraclass correlation coefficients range 0.43-0.99) and duration components of the TUG were valid to differentiate performance between patients with stroke and healthy persons 20 . Six portable 3 dimensional inertial sensors were placed at mid-thoracic, 5th lumbar vertebra, bilateral wrists and ankles 21 A gyroscope ( ± 400°/s range) and accelerometer ( ± 5g range) captured angular velocity and acceleration at the sampling rate of 200 Hz 22 .…”
Section: Data Collection and Analysismentioning
confidence: 99%